Hubungan tekanan darah dengan tingkat kecemasan pada pasien hipertensi - Sunarti, Sunarti; Hulu, Indah Kristiani; Sitorus, Desi Natalia; Harefa, Arnudin; Syuhada, Muhammad Taufiq (Holistik Jurnal Kesehatan, 2024)
Background: Hypertension is defined as a condition of persistent blood pressure with systolic pressure ≥140/90 mmHg. One of the factors that can cause hypertension is the level of anxiety experienced by patients. Therapy is necessary for hypertensive patients to manage their anxiety, one of which is through back and foot massage therapy, as many patients feel fear when experiencing hypertension for the first time. Purpose: To determine the relationship between blood pressure and anxiety levels in hypertensive patients. Method: This research is a quantitative study with a cross-sectional design, using both primary and secondary data. Data collection was carried out using observation sheets and questionnaires. The total population of this study consisted of 113 patients, with 30 respondents selected as the research sample. The sampling technique used was accidental sampling. The tool used to measure the patients' anxiety levels was a questionnaire with an ordinal scale. Data analysis was conducted univariately and bivariately, with the presentation of data from two variables analyzed using the chi-square test. Results: The findings revealed that 15 respondents (78.9%) who experienced mild anxiety had normal blood pressure, while 4 respondents (21.1%) had high blood pressure. None of the respondents with normal blood pressure experienced severe anxiety, while 11 respondents (100%) with high blood pressure also experienced severe anxiety. Statistical testing using the chi-square method showed a p-value of 0.001 (<0.05). Conclusion: There is a significant relationship between blood pressure and anxiety levels in hypertensive patients.   Keywords: Anxiety Level; Blood Pressure; Hypertension.   Pendahuluan: Hipertensi diartikan sebagai kondisi tekanan darah yang menetap dengan tekanan sistolik ≥140/90 mmHg. Salah satu faktor yang dapat menyebabkan hipertensi adalah tingkat kecemasan yang dialami oleh pasien. Diperlukan terapi bagi pasien hipertensi untuk mengelola kecemasan mereka, salah satunya melalui terapi pijat punggung dan kaki, karena banyak pasien merasa takut saat pertama kali mengalami hipertensi. Tujuan: Untuk mengetahui hubungan antara tekanan darah dan tingkat kecemasan pada pasien yang mengalami hipertensi. Metode: Penelitian ini merupakan penelitian kuantitatif dengan desain cross-sectional yang menggunakan data primer dan sekunder. Pengumpulan data dilakukan menggunakan lembar observasi dan kuesioner. Populasi penelitian ini berjumlah 113 pasien, dengan 30 responden yang dijadikan sampel penelitian. Teknik pengambilan sampel dilakukan dengan accidental sampling. Alat ukur yang digunakan untuk mengukur tingkat kecemasan pasien adalah kuesioner dengan skala ordinal. Analisis data dilakukan secara univariat dan bivariat, dengan penyajian data dari dua variabel dianalisis menggunakan uji chi-square. Hasil: Sebanyak 15 responden (78.9%) yang mengalami kecemasan ringan memiliki tekanan darah normal, sementara 4 responden (21.1%) memiliki tekanan darah tinggi. Tidak ada responden dengan tekanan darah normal yang mengalami kecemasan berat, sementara 11 responden (100%) yang memiliki tekanan darah tinggi juga mengalami kecemasan berat. Uji statistik dengan metode chi-square menunjukkan nilai p sebesar 0.001 (<0.05). Simpulan: Terdapat hubungan yang signifikan antara tekanan darah dan tingkat kecemasan pada pasien hipertensi.   Kata Kunci: Hipertensi; Tekanan Darah; Tingkat Kecemasan.